Pengaruh Shopping Orientation, Social Influence dan Perceived Ease of Use 1 Terhadap Keputusan Penggunaan Alikasi Dana - Nada kamilah; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2022)
This research aims to analyze the influence of Shopping Orientation, Social Influence, and Perceived Ease of Lise on the decision of use of Dana application in the Jabodetabek and The mination in this research were all rers of Dana application in the Jabodetabek urea. The sample se of 50 people with quantitative research methods and data collection techniques with actionmai The technique used this research is incidental sampling and purposive sampling which are part the non erabakijir sampling Based on the results of the 1 test analysis shows that Shop Ordion variable has no effect on the decision of the of Dana application. Whereas the Saddle cerceived Ease of Use variables àgnificantly influence on the decon of use of Dana application.